Inhibition of Mineralisation of Urinary Stone forming Minerals by L-Ascorbic Acid and Effect of Micronutrient Metal Ions on the Inhibition in Aqueous and Urinary Milieu - Rao, T.V.R.K.; Chaoudhry, V.K. (Asian Journal of Chemistry, 2010)
L-Ascorbic acid has been studied as inhibitor in the mineralisation of urinary stone forming minerals, viz., calcium phosphate, oxalate or carbonate. Inhibition efficiency has been studied in different experimental models. Effect of micronutrient metal ions, viz., Cr3+, Mn2+,Fe2+, Co2+, Ni2+, Cu2+ or Zn2+ on the inhibition efficiency of L-ascorbic acid has also been investigated in aqueous and urinary milieu. Utility of the results in urolithiasis inhibition has been discussed.